The earlier Mousterian in westernmost Iberia: geoarchaeology of Cobrinhos site in the Tejo River terrace staircase of Vila Velha de Ródão (Portugal - Pereira, Telmo (2019)
Cobrinhos is a Middle Paleolithic site found during the construction of a paper factory, in the winter of 2014, in Vila Velha do Ródão, Central inland Portugal. In this region, the staircase terraces has six steps (T1 to T6), but Paleolithic is only found in the T4, T5 and T6. The T4 is dated of ca. 340 ka to 155 ka, with Acheulean at the basal levels (ca. 340 to 325 ka), later Acheulean at the middle levels (ca. 325 to 200 ka) and early Mousterian at the upper levels (ca. 165 to 155 ka). Cobrinhos is in a colluvium that links to the top of the T4 terrace, has the same geochemical component (reddish clay-sand sediments) that characterizes the T1 to T4 terraces, which is considerably different from that of the T5 and T6. Despite disturbed by recent plowing, the site shows an evenly distribution of sizes and shapes of the lithic assemblage, thousands of implements <30mm, a coherence the Mousterian assemblage and absence of Acheulean or Upper Paleolithic-on tools. The lithic assemblage comprises extensive, intensive and pre-determinate reductions. Extensive reduction was opportunistic and aimed the production of large flakes that were used as without retouch and as cores. Intensive reduction was mostly centripetal and unipoloar unidireccional for the production of medium and small flakes. Pre-determinate reduction includes Levallois preferential, Levallois recurrent and Discoidal for the production of medium and small Levallois flakes and points, Pseudo-levalois points and blades. The combination of data suggests that the colluvium unit is coeval of the deposition of the T4 topmost deposits and that Cobrinhos is in its original geomorphological context. Based on these, we believe to be possible to establish a probable age of ca. 165 to 155 ka for the site, but, this age needs to be supported by more finite absolute ages to be gathered in the near future. These results are of relevance in the scope of the investigation about the demise of archaic Pleistocene human populations and the proliferation of Neanderthal groups.